Transmedial Narration: Narratives and Stories in Different Media - Elleström, Lars (Springer International Publishing, 2019)
This open access book is a methodical treatise on narration in different types of media. A theoretical rather than a historical study, Transmedial Narration is relevant for an understanding of narration in all times, including our own. By reconstructing the theoretical framework of transmedial narration, this book enables the inclusion of all kinds of communicative media forms on their own terms. -- -- The treatise is divided into three parts. Part I presents established and newly developed concepts that are vital for formulating a nuanced theoretical model of transmedial narration. Part II investigates the specific transmedial media characteristics that are most central for realizing narratives in a plenitude of different media types. Finally, Part III contains brief studies in which the narrative potentials of painting, instrumental music, mathematical equations, and guided tours are illuminated with the aid of the theoretical framework developed throughout the book. Suitable for advanced students and scholars, this book provides tools to disentangle the narrative potential of any form of communication. --
https://katalog.adlr.link/Record/51-9783030012939